2020
DOI: 10.21203/rs.3.rs-42898/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High prevalence of SARS-CoV-2 Infection Among Symptomatic Healthcare Workers in a large university tertiary hospital in São Paulo, Brazil

Abstract: Background: Latin America became the epicenter of the COVID-19 pandemic in May 2020, mostly driven by Brazil's situation. Healthcare workers are at increased risk of SARS-CoV-2 infection, experiencing a significant burden from COVID-19. Identifying and understanding the clinical characteristics and risk factors associated with infection are of paramount importance to inform screening strategies and infection control practices in this scenario. The aims of this study were to investigate the prevalence and clini… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 11 publications
1
17
2
Order By: Relevance
“…These findings show a higher infection rate than those previously reported in other countries, such as 11%, 8.8, and 7,1% in Spain, Italy, and Turkey, respectively 4 , 5 , 8 . However, Buonafine et al 9 in São Paulo, Brazil, reported 42.4% confirmed COVID-19 infections among symptomatic HCWs, while our findings demonstrated a 32.7% positivity rate among symptomatic HCWs.…”
contrasting
confidence: 78%
“…These findings show a higher infection rate than those previously reported in other countries, such as 11%, 8.8, and 7,1% in Spain, Italy, and Turkey, respectively 4 , 5 , 8 . However, Buonafine et al 9 in São Paulo, Brazil, reported 42.4% confirmed COVID-19 infections among symptomatic HCWs, while our findings demonstrated a 32.7% positivity rate among symptomatic HCWs.…”
contrasting
confidence: 78%
“…The mean or median age of subjects in the 104 studies ranged from 26 to 77 years. Studies reported on subjects from multiple countries (n=5), [15][16][17][18][19] from Australia (n=1), 20 Belgium (n=1), 21 Brazil (n=1), 22 Canada (n=2), 23,24 China (n=7), 2,19,[25][26][27][28][29] France (n=12), 19,[30][31][32][33][34][35][36][37][38][39] Germany (n=10), 19,[40][41][42][43][44][45][46] Greece (n=1), 49 Iceland (n=1), 50 India (n=2) 51,52 Iran (n=3), [53][54][55] Iraq (n=2), 56,57 Israel (n=4), [58][59][60][61] Italy (n=19),…”
Section: Resultsmentioning
confidence: 99%
“…The shelter workers evaluated in this study included healthcare and social assistance professionals, cooking, and maintenance personal. It has been well known that healthcare professionals are at a greater risk of exposure to SARS-CoV-2 than the general population [ 22 ]. Strikingly, the seroprevalence of 47.1% (41/87) reported herein is higher than those of healthcare workers from other countries, ranging from 0 to 45.3% in a systematic review of 49 studies from North America, Asia, Europe, and Africa [ 23 ].…”
Section: Discussionmentioning
confidence: 99%